2021
DOI: 10.1186/s12966-021-01191-y
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and sedentary behaviour in occupational and non-occupational settings: a systematic review with meta-analysis

Abstract: Background Sedentary behaviour (SB; time spent sitting) is associated with musculoskeletal pain (MSP) conditions; however, no prior systematic review has examined these associations according to SB domains. We synthesised evidence on occupational and non-occupational SB and MSP conditions. Methods Guided by a PRISMA protocol, eight databases (MEDLINE, CINAHL, PsycINFO, Web of Science, Scopus, Cochrane Library, SPORTDiscus, and AMED) and three grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 148 publications
(380 reference statements)
3
46
1
2
Order By: Relevance
“…Among late middle-aged and older adults in the Korean NHANES study, more time spent sitting—especially over 7 h—was associated with worse pain in the low back. These relationships were strongest among those engaging in the least leisure time physical activity ( 10 , 11 ). In a meta-analysis of pain and sedentary behavior, Dzakpasu ( 10 ) found that more sedentary time was associated with greater pain in general, as well as low back and knee pain.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among late middle-aged and older adults in the Korean NHANES study, more time spent sitting—especially over 7 h—was associated with worse pain in the low back. These relationships were strongest among those engaging in the least leisure time physical activity ( 10 , 11 ). In a meta-analysis of pain and sedentary behavior, Dzakpasu ( 10 ) found that more sedentary time was associated with greater pain in general, as well as low back and knee pain.…”
Section: Introductionmentioning
confidence: 98%
“…These relationships were strongest among those engaging in the least leisure time physical activity ( 10 , 11 ). In a meta-analysis of pain and sedentary behavior, Dzakpasu ( 10 ) found that more sedentary time was associated with greater pain in general, as well as low back and knee pain. In a longitudinal analysis of the relationships between accelerometer-measured sedentary time, MVPA, and pain among 199 women during and for 48-month following active breast cancer treatment, Dore and colleagues ( 12 ) found that more sedentary behavior was associated with increases in pain over time.…”
Section: Introductionmentioning
confidence: 98%
“…Dzakpasu et al demonstrated evidence to support significant associations between workplace sitting time and MSD in the neck, shoulders and lower back among office workers. This could be explained by static sitting posture for long periods of time that may produce tension, strain and fatigue in the muscles inducing MS pain and discomfort, and other chronic conditions [ 35 ]. Jun et al reviewed many prospective studies and found strong evidence demonstrated sitting for computer work ≥ 4 h/day was a risk factor for neck and shoulder pain among office workers (relative risk = 1.36, 95% CI 1.10–1.88) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review (Dzakpasu et al, 2021) analysing cross‐sectional studies found that sedentary behaviour (regardless of the measure) was associated with low back pain. However, they identified insufficient evidence from prospective cohort studies, which limited their analysis to a narrative description of findings.…”
Section: Discussionmentioning
confidence: 99%